A Problem in Ludwig Feuerbach's Theory of Religious Language - Foard, Lawrence C. (Religious studies, 1973)
The late Karl Barth once wrote that no one can hope to overcome Ludwig Feuerbach with whining or with angry criticism of his views of religion.' This is plainly correct, for Feuerbach's argument that religious language is always anthropological is an argument of great attractiveness—and, apparently, of great explanatory utility to psychologists, historians, and philosophers. Barth's solution to the problem raised by Feuerbach is less satisfactory. It just will not do for Christian believers simply to cleanse Christian theology of anthropological foundations by admitting that even in our relation to God, we can lay claim to his truth, his certainty, his salvation as grace and only as grace'. Nor will it do for Christian believers, secure in the promise of divine succour, to laugh at Feuerbach' for his naive view of human possibilities. Even though a cleansing of theology may be helpful to the Church, it will have little (more likely, no) effect upon the widespread popular and scholarly acceptance of Feuerbach's conclusions.